1991
DOI: 10.1111/j.1440-1673.1991.tb03047.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Transabdominal Ultrasound in the Measurement of Prostate Size

Abstract: Thirty-eight patients underwent transabdominal sonographic measurement of their prostate by two different sonographers. Prostatic weight was estimated by the ellipsoid method. In 47% of the cases the second estimate of weight was within 5g of the first and in 84% of cases the second estimate was within 10g of the first. 95% of the time the second estimate was within 16g of the first. The differences in estimated weight between the two observers ranged from 1g to 22g with a mean of 6g. The estimated prostatic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Besides, transrectal ultrasonography (TRUS) was adopted in these studies, which was different from us of TAUS. TAUS was believed to be less clearer in showing the margins of the prostate (Hough & List, 1991). But it has been reported that there were no significant differences between the two measurements (Huang Foen Chung et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Besides, transrectal ultrasonography (TRUS) was adopted in these studies, which was different from us of TAUS. TAUS was believed to be less clearer in showing the margins of the prostate (Hough & List, 1991). But it has been reported that there were no significant differences between the two measurements (Huang Foen Chung et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…The majority of the enucleated glands weighed less than 60 gm (71.7%) suggests the procedure of choice would have been transurethral resection of the prostate (TURP). [11] Surgeons can depend upon the findings of ultrasonography in selecting the appropriate treatment method for BPH patients. The correlation coefficient in several series generally shows a statistically significant correlation between prostatic volume measured on abdominal ultrasonography and the weight of the prostate removed at surgery, indicating that it is a useful tool for selecting the appropriate surgical approach.…”
Section: Discussionmentioning
confidence: 99%